2012
DOI: 10.3402/ijch.v71i0.18203
|View full text |Cite
|
Sign up to set email alerts
|

Mycoplasma genitaliumpresence, resistance and epidemiology in Greenland

Abstract: ObjectivesGreenland reports the highest rates of chlamydial infection and gonorrhea in the Arctic. Our objective was to determine the presence, and describe the basic epidemiology, of Mycoplasma genitalium for Greenland.Study designCross-sectional study.Methods314 residents from Nuuk and Sisimiut, between the ages of 15 and 65 years, participated in “Inuulluataarneq” (the Greenland Sexual Health Project) between July 2008 and November 2009. Participants provided self-collected samples for sexually transmitted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
79
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 90 publications
(85 citation statements)
references
References 34 publications
5
79
0
1
Order By: Relevance
“…The population used in the present study was selected from Inuulluataarneq (the Greenland Sexual Health Project), which included 314 residents (196 women and 118 men) from Nuuk and Sisimiut, Greenland, between July 2008 and November 2009. Participants were recruited from the general population via the population registry, by direct contact via telephone calls, and by advertising in local media as previously described (14). The initial objective of this study was to determine the epidemiology of sexually transmitted infections (STIs) (14) and BV in Greenland (10).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The population used in the present study was selected from Inuulluataarneq (the Greenland Sexual Health Project), which included 314 residents (196 women and 118 men) from Nuuk and Sisimiut, Greenland, between July 2008 and November 2009. Participants were recruited from the general population via the population registry, by direct contact via telephone calls, and by advertising in local media as previously described (14). The initial objective of this study was to determine the epidemiology of sexually transmitted infections (STIs) (14) and BV in Greenland (10).…”
Section: Methodsmentioning
confidence: 99%
“…Participants were recruited from the general population via the population registry, by direct contact via telephone calls, and by advertising in local media as previously described (14). The initial objective of this study was to determine the epidemiology of sexually transmitted infections (STIs) (14) and BV in Greenland (10). Each participant completed an interviewer-administered sexual health survey in either Greenlandic or Danish and provided a self-obtained vaginal smear, a vaginal swab sample collected with a flocked swab in UTM (Copan, Brescia, Italy), and an FVU sample collected in GeneLock transport medium (Sierra Molecular Corp., Sonora, CA) as previously described (14).…”
Section: Methodsmentioning
confidence: 99%
“…Macrolide-resistant M. genitalium isolates have been detected in patients from Australia, Sweden, Norway, and the United States, and mutations in domain V of the 23S rRNA gene have been detected in specimens from Greenland, Japan, France, and an increasing number of other countries (8,9,(12)(13)(14). The resistance mutations consist mainly of adenine-to-guanine mutations in the 23S rRNA gene at position 2058 or 2059 (Escherichia coli numbering) (9,12,15,16).…”
mentioning
confidence: 99%
“…The second component of Inuulluataarneq involved parent/guardian education regarding sexual health communication with their youth. Prior to the development, design, implementation and evaluation of Inuulluataarneq, we conducted a two-year exploratory study in Greenland (2007Greenland ( -2009, in which Kalaallit youth reported a lack of communication with parents or guardians about topics related to sex, such as STIs (Gesink et al, 2010;Gesink et al, 2012). The results from this study were used to develop Inuulluataarneq's parent/guardian component (Rink et al, 2012).…”
Section: Introductionmentioning
confidence: 99%